Analisis Tingkat Pengetahuan Masyarakat Tentang Upaya Pencegahan Dampak Polusi Udara terhadap Kesehatan Pernapasan di Kota Semarang - Azzahra Aulia Ramadhani; Mecca Shahha Hita; Imroatus Sholihah; Dian Nabella N.K; Vira Dwialvianti; Amelia Putri; Minda Amanda Puspa; Jelita Ambar Astuti; Satriya Pranata (PT. Saha Kreasi Indonesia, 2025)
Air pollution is a significant environmental health threat, particularly to the respiratory system in densely populated urban areas such as Semarang. Public understanding of the impacts and prevention of air pollution is key to respiratory health protection efforts. This study aims to analyze the level of public knowledge in Semarang City regarding efforts to prevent the impact of air pollution on respiratory health. This study used a quantitative descriptive design with a cross-sectional approach involving 100 respondents selected through purposive sampling technique with criteria of residing in Semarang and aged ≥18 years. Data were collected using structured questionnaires covering knowledge about air pollution causes, health impacts, and prevention strategies. Data analysis used descriptive statistics in the form of frequency distribution and percentages as well as Chi-Square test to identify relationships between variables. The results showed that the majority of respondents, 95%, had good knowledge about air pollution and its prevention efforts, while 5% had adequate knowledge, and no respondents had poor knowledge. This high level of knowledge was influenced by education level where 55% of respondents were university graduates, productive age with 67% of respondents aged less than 35 years, and length of residence in Semarang City with 62% of respondents having lived for more than 10 years. This study concludes that the community of Semarang City has good knowledge about efforts to prevent the impact of air pollution on respiratory health, and this knowledge serves as a foundation for the formation of better preventive attitudes and behaviors in facing air pollution threats.